An expression obtained from the square of binomial equation is a perfect square trinomial. An expression is said to a perfect square trinomial if it takes the form ax2 + bx + c and satisfies the condition b2 = 4ac. The perfect square formula takes the following forms: (ax)2 + 2abx + b2 = (ax + b)
: Let y = f(x) = x^1/3 Then dy = 1/3*x^(−2/3) dx Since f(64) = 4. We take x = 64 and dx = ∆x = 1 This gives dy = 1/3*(64)^(−2/3)* (1) = 1/48 ∴65^(1/3) = f(64 + 1) ≈ f(64) + dy = 4 + 1/48 ≈ 4.021 <span> </span>